2014
DOI: 10.17816/kmj1517
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of medical students to alcohol and nicotine

Abstract: Aim. To determine the attitude of medical students to alcohol and nicotine. Methods. An anonymous survey of 118 5th year students (43 male students, 75 female students; mean age 22.6±0.9 years) of Irkutsk State Medical University was conducted. A self-composed questionnaire allowing to evaluate the students’ attitude to alcohol and nicotine was used. No cases of turndown were observed. Results. 17 (39.5%) out of 43 male students and 31 (41.3%) out of 75 female students were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was shown that factors associated with a healthy lifestyle prevent the development of emotional burnout [4,8,[13][14][15]. On the contrary, factors associated with an unhealthy lifestyle (alcohol and coffee consumption, insomnia, lack of vacation) cause burnout [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that factors associated with a healthy lifestyle prevent the development of emotional burnout [4,8,[13][14][15]. On the contrary, factors associated with an unhealthy lifestyle (alcohol and coffee consumption, insomnia, lack of vacation) cause burnout [16][17][18].…”
Section: Introductionmentioning
confidence: 99%